Frontispiece: Enlightening the "Spirit Molecule": Photomodulation of the 5‐HT2A Receptor by a Light‐Controllable N, N‐Dimethyltryptamine Derivative. Issue 26 (20th June 2022) - Gerwe, Hubert; He, Feng; Pottie, Eline; Stove, Christophe; Decker, Michael
Abstract : Neurochemistry The photomodulation of the 5‐HT2A receptor by a light‐controllable N, N ‐dimethyltryptamine derivative is reported by Michael Decker et al. in their Communication (e202203034 ).